Unemployment and Its Role in Increasing Crime Rates within the Iraqi Society (Medico Legal Update, 2020)
Unemployment is a complex problem whose dimensions and effects are not confined to the economic aspect solely, but also extend to the political, social, cultural and security aspects. It has great consequences, the first of which is crime and the increase of its rates. Perhaps there is a big difference between the developing communities that are still suffering from economic crises and instability in most fields of life, and suffer from chronic unemployment, which almost takes the form of the heavy legacy passed down from one generation to the next and the developed communities that are thinking of the need to exploit leisure time ideally through the creation of more future job opportunities and the importance of providing generous pensions for aged groups, not to mention the development of service sectors, especially health services and increasing the percentage of those covered by health care and health insurance services. Perhaps the difference between these and those is the attraction factor of security stability, which is the most effective tool for crime prevention and control, rather than the huge money spent by developing communities in building and arming the security